2003
DOI: 10.4161/cbt.2.5.450
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Genes and Resistance to Cancer Therapy: What Does the Experimental and Clinical Data Tell Us?

Abstract: The dominant paradigm in cancer treatment is that cancer cells die from the common pathway of apoptosis subsequent to DNA damage by anticancer agents and that cells resistant to apoptosis are resistant to therapy. In this review we trace the logic that brought about this view and discuss whether the clinical and experimental data that have now accumulated over the past decade support the position. We show that there is support for the apoptosis model only for certain malignancies of hematopoietic origin. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 142 publications
(162 reference statements)
3
77
0
Order By: Relevance
“…Effects that have been proposed in this regard include altered gene expression resulting from aberrant DNA cytosine methylation (23), centrosome amplification leading to multipolar mitosis (24), and self-sustaining production of hydrogen peroxide and elevated oxidative stress associated with mitochondrial dysfunction (25). Indeed, the question of how IR kills cells, with its important implications for radiotherapy, is a matter of continuing debate (26,27). The parallel that we find between radiosensitivity and anti-oxidant status may well extend to diverse animal species and cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Effects that have been proposed in this regard include altered gene expression resulting from aberrant DNA cytosine methylation (23), centrosome amplification leading to multipolar mitosis (24), and self-sustaining production of hydrogen peroxide and elevated oxidative stress associated with mitochondrial dysfunction (25). Indeed, the question of how IR kills cells, with its important implications for radiotherapy, is a matter of continuing debate (26,27). The parallel that we find between radiosensitivity and anti-oxidant status may well extend to diverse animal species and cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, to our knowledge, these response pathways have not been investigated concurrently in a single pre-clinical or clinical study that would correlate these end points with tumor response or overall survival. It has been suggested that apoptosis is an insufficient measure of the response of tumors to therapy (Brown and Wouters, 1999;Brown and Wilson, 2003). Our current understanding points to significant cross-talk among different response pathways.…”
Section: Clinical Relevance Of Cell Death Pathwaysmentioning
confidence: 95%
“…Clinical studies have not definitively indicated that apoptosis is primarily responsible for tumor responses (Brown and Wouters, 1999;Brown and Wilson, 2003). Although these clinical data are not in conflict with the recognized role that evasion of apoptosis has in tumorigenesis (Hanahan and Weinberg, 2000), some pre-clinical data challenge the proposition that apoptosis is the only mediator of treatment response (Brown and Wouters, 2001).…”
Section: Treatment-induced Response Pathways: Apoptosis and Beyondmentioning
confidence: 99%
“…They induce p53 activation and apoptosis, 32,33 and induction of apoptosis has been shown to be a key determinant of drug response in AML. 34 Meanwhile, AraC and doxorubicin cause cell cycle arrest in S-and G 2 /M-phases, respectively. 35,36 Our findings suggest that the cell cycle arrest induced by AraC or doxorubicin would not protect leukemia cells from p53-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%